Discovering the Relationship Between Science Students' Critical Thinking and Collaborative Problem Solving in Higher Education: Theoretical, Empirical, and Determining Factors - An Nuril Maulida Fauziah; Wahyu Budi Sabtiawan; Angela Boey (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study investigates the robust positive correlation between critical thinking (CT) and collaborative problem-solving (CPS) in science education. Employing a convergent parallel mixed methods design, the study involved a sample of 231 undergraduate students from Islamic higher education. Linear regression analysis demonstrated that CT accounted for 74.20% of the variance in CPS. The study underwent three complementary analytical phases. In the theoretical phase, prior literature was reviewed to contextualize CT and CPS. In the empirical phase, quantitative data were analyzed using regression, confirming the strong association between CT and CPS in the context of science education. In the factor-identification phase, qualitative coding revealed enabling and constraining factors. Enablers included AI tools (e.g., ChatGPT), conducive environments, hands-on practice, and targeted training, while barriers included personal biases, time constraints, and team conflicts. This research contributes by employing a convergent mixed-methods design in the Islamic higher education science context, integrating regression with qualitative factor analysis. These findings provide actionable guidance for designing integrated pedagogical strategies that promote both CT and CPS.